Cross-Cultural Student Teaching: Examining the Meaning-Making of one White, Female, MiddleClass Preservice Teacher - Shedrow, Stephanie J. (Journal of International Students, 2017)
While teacher educators implement diverse student teaching placements for preservice teachers as a means of bridging the cultural mismatch in classrooms around the United States, researchers have only recently begun to tap into the role that preservice teachers’ “whiteness” plays in their ideologies. As such, the purpose of this study was to better understand how one white, female preservice teacher made meaning of her experiences during a cross-cultural experiential learning (CCEL) student teaching placement abroad. Analyzing if and how previous intercultural interactions were drawn upon while abroad, as well as how experiences abroad were employed once returning to the US, findings suggest that cultural competency does not directly equate to recognizing whiteness and the privileges associated.